THE EFFECT OF SALES AND CORPORATE SOCIAL RESPONSIBILITY ON THE TAX PLANNING SECTOR LQ45 FOR THE 2020-2021 PERIOD - Russel Richard Michael Frans; Ronny Buha Sihotang (Jurnal Ekonomi, 2023)
The study was conducted to confirm the effect of sales and corporate social responsibility on LQ45 company tax planning during two years of research for thirty-nine companies with a total of seventy-eight samples using purposive sampling in the collection method. Researchers used the descriptive analysis method with multiple linear regression. The results show that sales have a significant positive effect on tax planning, and corporate social responsibility has no impact on tax planning; simultaneously, sales and corporate social responsibility affect tax planning.